An Analysis of Lexicons in Pendet Dance Movements - Pradnyani, Pande Eka Putri; Budasi, I Gede; Agustini, Dewa Ayu Eka (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2023)
Along with the development of the times, Balinese language and culture began to be abandoned. It is important to conduct a new study of the lexicon in art as a means of keeping the Balinese language well preserved. Therefore this study analyzed the lexicons in Pendet dance movements to respond to the Balinese language endangerment status. This study is designed in descriptive qualitative research which focused on Pendet dance lexicons as research objects. To collect the data regarding the lexicons, an observation sheet, and an interview guide were used as the instruments. The results show that there are 36 (thirty-six) lexicons in the Pendet dance. The obtained lexicons were then categorized into seven types based on body parts, namely leg movement (8), hand movement (6), finger movement (4), body movement (9), neck movement (1), eye movement (4), and expressions (4). The series of lexicons in Pendet dance have a cultural meaning which represents the beauty of Balinese women and their friendly characteristics. Thus, this study can give implications in linguistics study as preservation of the Balinese language.